Design and development of a marker-based augmented reality system using OpenCV and OpenGL - Yap, H.J.; Taha, Z.; Eng, T.H.; Chew, J.Y. (2009)
Augmented reality system generates a composite view for the user. It is a combination of the real scene viewed by the user and a virtual scene generated by the computer. In this paper, a webcam based augmented reality system has been developed using OpenCV and OpenCL. Webcam is used to capture the marker tag and image processing technique is used to obtain the required information such as position and orientation. By using this information, virtual images or objects can be created and "pasted" on the marker tag. OpenCV is used to handle real-time image processing and virtual objects are drawn using OpenCL API. The design and development of the system mainly involves the design of the marker tag. The design criteria of the marker tag have been studied, e.g. shape and colour. An effective market tag has been designed and used to provide the information about the position and orientation to the virtual environment. Virtual objects are drawn and superimposed with the real-time video captured from the webcam. The virtual objects can be changed through keyboard functions or 3D models in STL ASCII format.